ELEMENTS OF MATHEMATICAL LOGIC AND THEIR PROBLEMS - Abdimomin Abdurakhmanov; Normaxmatov Shogzod (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
These considerations serve as the main objects of investigation in the section called algebra of mathematical logic. It is interesting to look at the meaning of each statement of mathematical logic,whether it is true, true, true or false.Thus, in mathematical logic, it is said: "Every statement has the property of being either true or false."